PERSEPSI MAHASISWA TERHADAP PEMAHAMAN KONSEP MATA KULIAH STATISTIKA LANJUT - Munasiah, Munasiah; Astuti, Lin Suciani; Heriyati, Heriyati (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2024)
Advanced Statistics is one of the courses that students must take in the fifth semester. This course is also a course that students are less interested in because it is related to calculations and cannot be separated from basic mathematical skills. Because of student assumptions regarding this matter, students have a low (negative) perception of this course. Negative perceptions from students cause a lack of student enthusiasm and motivation in studying advanced statistics, so that students' understanding of advanced statistics is also low. This research aims to find out how much influence students' perceptions have on their understanding of advanced statistics. The method of this research took the form of a survey and question instrument given to 50 students. The results of this research are that there is an influence on student perceptions on understanding advanced statistics courses.